2020
DOI: 10.1177/0194599820917631
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Stimulation Therapy in Obstructive Sleep Apnea: A Systematic Review and Meta‐analysis

Abstract: Objective To evaluate the treatment efficacy of transcutaneous electrical nerve stimulation (TENS) in patients with obstructive sleep apnea (OSA). Data Sources Primary studies were identified though PubMed, Scopus, OVID, and Cochrane Library. Review Methods Systematic review was conducted by querying databases for articles published through July 2019. The search identified randomized controlled trial, randomized comparison, or observational studies pertaining to TENS treatment for OSA. Meta-analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A recent study identified the physiological traits predictive of a good response to treatment: a low arousal threshold and loop gain, and occurrence of muscle compensation [59]. The HSN treatment has revived interest in transcutaneous electrical stimulation, which would have the advantage of eliminating surgery, but is less effective than HSN [60,61].…”
Section: Hypoglossal Nerve Stimulation (Hsn)mentioning
confidence: 99%
“…A recent study identified the physiological traits predictive of a good response to treatment: a low arousal threshold and loop gain, and occurrence of muscle compensation [59]. The HSN treatment has revived interest in transcutaneous electrical stimulation, which would have the advantage of eliminating surgery, but is less effective than HSN [60,61].…”
Section: Hypoglossal Nerve Stimulation (Hsn)mentioning
confidence: 99%
“…"training" the tongue muscles), such stimulation results in an improvement in post-treatment AHI. However, the impact on quality of life remains unclear [174]. Electrical stimulation has also been applied to the muscles of the tongue to cause muscle contraction and increase strength and fatigue resistance and has been shown to reduce time spent snoring [175].…”
Section: Other Stimulation Techniquesmentioning
confidence: 99%
“…Two adhesive electrode patches were placed onto the skin of the submental area which is halfway between the chin and the angle of the mental region. With a little battery power, transcutaneous electrical stimulation was delivered to the submental skin to activate the motor unit of the dilators of the upper airway by stimulating the underlying nerve [ 123 ]. In a randomized, sham-controlled trial, the mean AHI after one-night transcutaneous electrical stimulation was reduced by 9.1 from 28.1 while the sham stimulation had a modest reduction of AHI by 4.1 from 19.5 [ 124 ].…”
Section: Treatment Of Osamentioning
confidence: 99%
“…TES showed less treatment efficiency than HGNS, but it was much more cost-effective and had almost no adverse events besides minor local skin irritation. TES had a similar stimulation methodology with HGNS that it would be used for predicting the treatment success of HGNS in patients with OSA before undergoing an invasive surgery [ 123 ]. Moreover, the TES is a non-invasive therapy that avoids complex surgical procedures, and the proof-of-concept outcome for patients with OSA is promising, even it has not been implemented into clinical management yet.…”
Section: Treatment Of Osamentioning
confidence: 99%